Guidelines for Risk Management of Enhancing Efficiency in School Operation under the Pathum Thani Primary Educational Service Area Office - แก้วศรี, ปนัดดา; รังรองรัตน์, รุ่งอรุณ (Journal of Educational Review Faculty of Education in MCU, 2018)
The objectives of this research were to: 1) study current conditions and desirable conditions of risk management on enhancing efficiency in school operation under the Pathum Thani Primary Educational Service Area Office, 2) study the essential needs for risk management on enhancing efficiency in school operation under the Pathum Thani Primary Educational Service Area Office, and 3) propose risk management guidelines of enhancing efficiency in school operation under the Pathum Thani Primary Educational Service Area Office. The sample of this research was 311 school administrators and 346 teachers, selected by simple random sampling consisting of. The research instrument included a 31-item, 5-rating scale questionnaire with the reliability at 0.976 and a semi-structured interview. Frequency, percentage, arithmetic mean and content analysis with PNI Modified were used for data analysis. This result revealed that risk management guidelines on enhancing efficiency in school operation under the Pathum Thani Primary Educational Service Area Office were as follows: 1) monitor and control, 2) identification and analysis, 3) assessment, 4) treatment and information technology, and 5) policy and objective setting.